Prenatal detection and postnatal verification of unusual Intracardiac Total Anomolous Pulmonary Venous Connection (TAPVC) in complex heart defect with dextrocardia - case report - Krasoń, Aneta; Płużańska, Joanna; Łukaszewski, Maciej; Moll, Jadwiga; Respondek-Liberska, Maria (Prenatal Cardiology, 2018)
Prenatal diagnosis of total anomolous pulmonary venous connection (intracardiac) was diagnosed in fetus with dextrocardia and complex heart defect, which allowed fetal echocardiography monitoring, planning the time and place for delivery as well as early cardiac surgery. The differences between prenatal and postnatal evaluations were underlined. Despite life treathening condition neonate was asymptomatic without any heart murmur for the first 3 days after delivery.